2020
DOI: 10.4209/aaqr.2020.04.0170
|View full text |Cite
|
Sign up to set email alerts
|

Recent Improvement in Particulate Matter (PM) Pollution in Ulaanbaatar, Mongolia

Abstract: Ulaanbaatar, the capital city of Mongolia, has occasionally been considered the most polluted city in the world. Approximately 46% of the population resides in Ulaanbaatar, and over half of the population living in ger (traditional yurt dwelling) areas consumes raw coal, which leads to an increase in ambient air pollutants. The Government of Mongolia took a series of actions to reduce air pollution; one was the ban on the consumption of raw coal beginning on 15 May 2019. In this study, improvement in particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 15 publications
4
17
0
Order By: Relevance
“…However, the fact that the amount of PM2.5 concentration significantly decreased compared to previous years was not due to the COVID outbreak related actions but it was thanks to Resolution 62 of the Mongolian government, which banned the burning of raw coal and required only the use of coal by-product. In another study, it was also found that the concentration of PM10 and PM2.5 during winter 2019-2020 decreased by 46-55 per cent, compared to previous years [16], which complies with our study as well.…”
Section: Pmassupporting
confidence: 92%
“…However, the fact that the amount of PM2.5 concentration significantly decreased compared to previous years was not due to the COVID outbreak related actions but it was thanks to Resolution 62 of the Mongolian government, which banned the burning of raw coal and required only the use of coal by-product. In another study, it was also found that the concentration of PM10 and PM2.5 during winter 2019-2020 decreased by 46-55 per cent, compared to previous years [16], which complies with our study as well.…”
Section: Pmassupporting
confidence: 92%
“…Changing the fuel did not address the underlying need for a more sustainable, comprehensive form of heating infrastructure throughout the ger districts. While it has been reported that there was a subsequent improvement in particulate matter pollution that winter in Ulaanbaatar (Ganbat et al 2020), the coal briquette solution-arguably a lot cheaper to implement than centrallysupplied heating infrastructure-offset the costs on to ger district residents.…”
Section: Managing Air Pollution In Ulaanbaatarmentioning
confidence: 99%
“…Air pollution has become the third leading cause of death in Mongolia [13]. Frequent heavy smog incidents in Mongolia have attracted widespread public attention [14][15][16][17], and it has been reported that Mongolian children exposed to air pollution have poorer lung development and a higher prevalence of asthma [18,19]. Air pollution also negatively affects fetal growth, leading to low birth weight and preterm birth [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The Mongolian government has made great efforts to solve the air pollution problem in UB. For example, MNT 164.1 billion and USD 104.7 million were invested in reducing air pollution between 2008 and 2016 [17]. On May 15, 2019, the Mongolian government implemented a ban on the burning of raw coal by UB households, and supplied "refined briquette" at a subsidized price close to that of raw coal; thus, the air quality is expected to improve.…”
Section: Introductionmentioning
confidence: 99%